Precision Pain Management in Interventional Radiology: A Systematic Review - Al Sayegh, Mohammad (Galen Medical Journal, 2025)
Chronic pain, as a complex and individual phenomenon, still represents a significant issue in both the acute and chronic contexts. This study aimed to investigate the current state of pain management in IR procedures and identify potential areas for improvement in the standardization of pain management protocols. IR approaches are less invasive and focus on individualized treatment targeting the cause of pain, especially in chronic pain states. Precision pain medicine aims to tailor treatment plans based on algorithms grounded in evidence to address the needs of patients. This systematic review aims to assess the effectiveness of IR in precision pain management by analyzing its techniques, safety, and clinical outcomes. In light of the existing literature, this review aims to fill the knowledge gap, call for protocol harmonization, and demonstrate how IR can contribute to patient-centered care. The results are expected to contribute to the knowledge base, inform future research and clinical practice, and improve patients’ quality of life with multiple pain conditions.